Comprehensive Exploration of Three Pistachio Varieties: Antidiabetic, Anticholinergic, Antioxidant Properties, Phytochemical Profile by LC-MS/MS, and Molecular Docking - Izol, Ebubekir; Beltekin, Busra; Turhan, Munire; Karakoc, Sirvan; Necip, Adem; Yilmaz, Mustafa Abdullah; Cakir, Oguz (Wiley, 2026)
Pistachios (Pistacia vera L.) are a significant food that is added to many foods and also consumed as a snack. The kernel part is consumed very much. In this study, 53 phytochemical constituents of three pistachio varieties (Halebi, K & imath;rm & imath;z & imath;, and Uzun) were profiled by LC-MS/MS, and their antioxidant capacity (total phenolic and flavonoid content, ABTS, DPPH, CUPRAC, FRAP, MCA, and phosphomolybdenum assays), antidiabetic activity (alpha-amylase and alpha-glucosidase inhibition), anticholinergic activity (AChE and BChE inhibition), and wound healing potential (tyrosinase inhibition) were evaluated. Additionally, molecular docking was used to examine the binding interactions of the major phytochemicals with each enzyme. The major phytochemical ingredients were tannic acid (24.005 mg/g), catechin (11.284 mg/g), protocatechuic acid (6.202 mg/g), gallic acid (5.717 mg/g), epicatechin gallate (1.686 mg/g), and epigallocatechin gallate (1.139 mg). The highest antioxidant properties were obtained in the Uzun variety in all assays. Antioxidant properties were high in all three varieties. While wound healing potential was high across all three varieties (30-43 mg GALAE/g), their anticholinesterase (2.06-2.54 mg GALAE/g) and antidiabetic activities (0.64-2.94 mmol ACAE/g) were comparatively low. Major bioactive phytochemicals were discovered to have highly favorable docking scores. This study determined that three types of pistachios contain significant bioactive compounds and are a very nutritious food due to the diversity of their biological activities.
Keywords: antioxidant activity; enzyme inhibitory activity; molecular docking; phytochemicals; Pistacia vera